Comparison between various strain from Klebsiella pneumoniea on Nitrogen fixation - Fawz Abdul Salam K.AL-Saffar; Abdul Razak K. Mahmood; Najwa I. AL- Barhawi (Tikrit Journal of Pure Science, 2023)
Twenty one  isolates of K. Pneumonia isolated from infected pneumonic patients in Leicester city hospital in Britain, with  K. pneumonia342 standard strain which obtained from Prof. Jean-Marc in Leicester British  university were used in this study . These isolates were tested by inoculating in Nitrogen free broth medium .The results revealed variation in their growing and from Danken test it was appeared that the 18th isolate gave the best growth in comparison with the rest, then the 20th ,19 th isolates respectively.  While in respect to nitrogen fixation, the results showed variation in it's efficiency for it's nitrogen fixation, the 18th bacterial isolate was the  best according to it's fixation ,depending on measuring the activity of nitrogenase enzyme by Nesler reagent  ,then 20th,19th isolates  respectively.